Somatic and axonal LIGHT signaling elicit degenerative and regenerative responses in motoneurons, respectively. (25th March 2014) - Otsmane, Belkacem; Moumen, Anice; Aebischer, Julianne; Coque, Emmanuelle; Sar, Chamroeun; Sunyach, Claire; Salsac, Céline; Valmier, Jean; Salinas, Sara; Bowerman, Melissa; Raoul, Cédric
Synopsis <boxed-text content-type="graphic" id="embr201337948-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Activation of the LIGHT receptor LT‐βR in the somatic compartment of motoneurons elicits death, while activation in the axonal compartment stimulates axon outgrowth and branching. LIGHT also promotes functional recovery following peripheral nerve lesion. Somatic activation of LIGHT‐LT‐βR signaling triggers motoneuron death, while axonal activation increases motoneuron axon length and branching. LIGHT‐induced axon outgrowth and branching depend on ERK and caspase‐9 pathways Following peripheral nerve injury, LIGHT is required for reinnervation and functional recovery.